UNIMAS MOOC: Fundamentals of Management - Rohaya, Mohd Noor; Mohd Uzairi, Ahmad Hajazi; Muhammad Hafiz, Mohd Shukri (UNIMAS MOOC, 2017)
https://www.openlearning.com/courses/fundamentals-of-management-unimas